Scientific Reasoning: Theory Evidence Coordination in Physics-based and Non-physics-based Tasks. Issue 2 (3rd May 2016) - Ibrahim, Bashirah; Ding, Lin; Mollohan, Katherine N.; Stammen, Andria
Abstract : Scientific reasoning is crucial to any scientific discipline. One sub-skill particularly relevant to the scientific enterprise is theory evidence coordination. This study, underpinned by Kuhn's framework for scientific reasoning, investigates how university students coordinate their self-generated theory and evidence in a physics topic (energy) and in non-content specific (non-physics-based) situations. Twenty-seven students completed five written reasoning tasks, three of which deal with energy concepts (physics-based) and two tasks concern with non-physics-based situations. The analysis focused on: (a) the completeness and correctness of the theory; (b) the source of the evidence; (c) theory evidence coordination or non-coordination; and (d) if coordination occurs, whether the evidence supports or refutes the theory, and the quality of students' explanations. The outcomes revealed that the students tended to coordinate theory and evidence for non-physics tasks as opposed to physics problems. When theory evidence coordination occurred, regardless of the type of scenarios, the evidence primarily supported the theory in the form of a poor explanation. The importance of content knowledge for scientific reasoning is discussed. The implications for applying scientific reasoning as an assessment tool in science are also highlighted.